AS EURASIA LOGISTICS CENTER LOGISTICS COMPETENCE OF TURKEY ACCORDING TO THE LOGISTICS PERFORMANCE INDEX COMPARATIVE REVIEW - ALPASLANOĞLU, Alpaslan (Atlas Journal, 2021)
Logistics is an extremely important and strategic sector for both the world and all countries, and it has been one of the leading international competition areas for countries. The Logistics Performance Index (LPI) made by the World Bank has become an important benchmark for this important competitive field, measuring and rating logistics competencies and performances. The aim of the research is to reveal the high level of economic and strategic advantages of Turkey, especially with its unique and unrivaled transportation and logistics potentials. High logistics performance is seen as necessary and important for Turkey, as well as for all countries, in terms of economy and strategy. In this study, which examines the logistics performance of Turkey in the Eurasian region, the importance of this study is to investigate the logistics competencies and potentials that can connect the continents of Europe and Asia and therefore become the logistics center of the Eurasian region. In this quantitative study using secondary type data; It was used as a criterion based on the Logistics Performance Index, which was created by the World Bank, announced every two years and consisted of 6 periods in total. The Index in question is the most effective, reliable and dominant Index in terms of measuring the logistics quality and competencies of countries, comparing them with each other and ranking them. Since the official data disclosed to the public by the World Bank, the United Nations organization, is used in the study; There is an extremely high level of competence in terms of validity, reliability and ethics. As a result of the research, it has been observed that although Turkey’s logistics competencies are behind the European region average, they are above the Asian, Eurasian and World logistics competencies average. However, it has been observed that Turkey’s logistics performance has been in a downward trend since the 2012 period, and has almost regressed to the 2007 LPI level in the last LPI period (2018). Despite this, it is thought that Turkey may become the most important logistics center in the Eurasian region with the evaluation of its transportation and logistics potentials. For this purpose, it has been concluded that Turkey needs to create globally integrated logistics centers, especially with its water and rail infrastructure, which are the main modes of transportation.